Mobile Money Use, Digital Banking Services and Velocity of Money in Ghana - Ocansey, Evans N. N. D.; Dadzie, Philomena; Nambie, Nicholas Bamegne (International Journal of Economics and Financial Issues, 2024)
Investigating the correlation between digital financial services, mobile money usage, and money velocity in Ghana, the study analysed time series data spanning from 1992 to 2022. A composite index was constructed by principal component analysis using data extracted from the world development indicators, with the components mobile money usage, digital financial services, and velocity of money. The estimation utilised an impulse response function and vector error correction model; the results indicated that mobile money, digital financial services, and money velocity are related in both the short and long term. Furthermore, the application of a standard deviation innovation to the velocity of money produced increases of both positive and negative magnitude for all the variables. This suggests that mobile money, digital banking services, and velocity of money in Ghana are interdependent in an asymmetric manner. In order to facilitate an increase in the velocity of money, the research concluded that policymakers should guarantee that a greater proportion of the population has access to mobile money and digital banking services. In addition to promoting mobile money, online banking services, and digital payment methods on purpose, the government should reduce reliance on physical currency and expedite the circulation of money. It is recommended that future longitudinal studies involving African nations employ diverse estimation techniques.